COMPARISON ANALYSIS OF PROFIT CALCULATION ACCOUNTING TREATMENT BETWEEN SHARIA PEGADAIANS AND CONVENTIONAL PEGADAIANS - Sabra B. Wahab; Iriany Dewi Soleiman (Jurnal Scientia, 2023)
Sharia pawnshops as a sharia-based financial institution are required to use sharia-based accounting tools. By operating a sharia-based business, of course, it will require accounting practices that can answer accounting problems in accordance with sharia, while conventional pawnshops only carry out a debt agreement contract with collateral for movable property. The purpose of this research is to find out the differences in the accounting treatment of profit calculations between sharia and conventional pawnshops. The research approach uses descriptive comparative by comparing the pawn accounting treatment from sharia and conventional perspectives. The data used includes primary data in the form of direct interviews with the company appointed as an informant. Secondary data in the form of data obtained from the company's internal. The analysis of the recognized sharia pawn accounting treatment is ijarah income which is calculated based on a predetermined rate from the estimated yield of pawned goods for a period of 10 days, the basis for recognizing income is a cash basis. Meanwhile, income recognized in conventional mortgages is recognized as capital/interest rental income which is calculated based on the amount of the loan granted for a period of 15 days, the basis for recognition of income is accrual basis. The results of the study show that the amount of profit is influenced by the amount of loan interest and ijaroh fees. Pawn Syariah does not use loan lease methods and fiduciary practices to make a profit.